Wound, pressure ulcer and burn guidelines – 6: Guidelines for the management of burns, second edition. Issue 11 (28th April 2020) - Yoshino, Yuichiro; Hashimoto, Akira; Ikegami, Ryuta; Irisawa, Ryokichi; Kanoh, Hiroyuki; Sakurai, Eiichi; Nakanishi, Takeshi; Maekawa, Takeo; Tachibana, Takao; Amano, Masahiro; Hayashi, Masahiro; Ishii, Takayuki; et al.
Abstract: "Wound, pressure ulcer and burn guidelines – 6: Guidelines for the management of burns, second edition" is revised from the first edition which was published in the Japanese Journal of Dermatology in 2016. The guidelines were drafted by the Wound, Pressure Ulcer and Burn Guidelines Drafting Committee delegated by the Japanese Dermatological Association, and intend to facilitate physicians' clinical decisions in preventing, diagnosing and treating burn injury. All sections are updated by collecting documents published since the publication of the first edition. Especially, the recommendation levels of dressing materials newly covered by the Japanese national health insurance are mentioned. In addition, the clinical questions (CQ) regarding the initial treatment of electrical (CQ15) and chemical burns (CQ16), and also the use of escharotomy (CQ22), are newly created.